A REVIEW ON ROLE OF UTTAR BASTI IN THE MANAGEMENT OF ERECTILE DYSFUNCTION (AYUSHDHARA, 2019)
In Ayurveda classics, Klaibya refers to erectile dysfunction i.e., a man who is unable to perform satisfactory sexual intercourse. Various Acharyas has mentioned different causes of the Klabiya likes psychogenic, neurogenic, vascular pathological factors. Male sexual dysfunctions are the most common of the psychosexual disorders in clinical practice. It refers to a problem during any phase of the sexual response cycle that prevents the man from experiencing satisfaction from the activity. Mainly Dhwajabhangaja Klaibya can be compared with the erectile dysfunction on the basis of symptoms. Basti is unique form of treatment modality that not only expels the vitiated Doshas rapidly but also nourishes the body. Charaka considered Basti as Ardhachikitsa, Uttarbasti is an important Panchakarma procedure where the medicated oil, Ghrita or decoction is administered into urinary bladder or uterus and is indicated in genito-urinary disorders of both male and female. Uttarbasti is the prime line of treatment in the case of Klaibya; it deliberates to overcome the Dhatukshaya, Shukrakshaya and Jara-avastha. Probably Uttarbasti acts by following mechanisms first pass metabolism, bladder permeability barrier, neurological stimulation, psychological stimulation. In the results of aphrodisiacs as well as rejuvenation therapy (i.e., Uttarbasti) and medication therapies are more effects on erectile dysfunction that may helps in process of erection.